Repair of Bovine and Equine Mandibular Fractures - Murch, K. M. (1980)
Clinical findings, surgical repair and postsurgical care of a unilateral fracture of the mandible of a bull and of a bilateral mandibular fracture in a horse are described. Compression plating limited the pain suffered by the animals and resulted in a quick return to function of the mandibles.